Learning from 'Panosikoma': Atelier 66's Additions to Ordinary Houses. Issue 1 (14th December 2018) - Magouliotis, Nikolaos
Abstract : The work of the Athens-based architectural practice Atelier 66 (est. 1965) has been extensively examined by local and international historiography over the past few decades. Most analyses have focused on the office's large-scale projects and have associated them with post-war architectural genealogies such as Team X or Critical Regionalism and, more recently, postmodernism. This article focuses on a set of less acclaimed projects within their extensive oeuvre, namely the small-scale additions to existing houses commonly known as 'panosikoma'. Based on a series of publications on this topic by Atelier 66 from the mid-1970s to the mid-1980s, and on recent interviews with the architects, the article situates Atelier 66's work in the specific technical and socio-economic conditions of the Greek post-war building boom. It shows how Atelier 66 related to ordinary processes and typologies of housing production in Greece ( antiparochi, polykatoikia and panosikoma ). Through these minor commissions, the architects theorized and developed their distinct approach to incremental housing via subsequent projects and publications. By concentrating on their 'ordinary house additions', this article aims to unsettle the established historiographical reception of Atelier 66 and invite further interpretations of their work.